The Relationship Between Student Economic Status and Motivation to Study at Higher Education in Padangsidimpuan - Siregar, Fitri Salsabila; Ahmad Ramadhan (Nusantara: Journal of Cultural Research, 2025)
This research aims to explore and explain the relationship between students' economic conditions and the spirit of learning at universities in Padangsidimpuan.  The methodology applied is descriptive qualitative, using a case study approach.  The informants in this study consisted of 10 students from diverse economic backgrounds, who were selected using purposive sampling method.  Information was obtained through in-depth interviews and observations of the students' academic and social environments.  The data analysis process was conducted through data reduction, data presentation, and conclusion drawing techniques.  The research findings indicate that students' economic conditions have an impact on their learning motivation.  Students who come from lower economic backgrounds often experience more difficulties in maintaining learning motivation, due to limited access to educational facilities and financial demands.  In contrast, students with better economic conditions have easier access to resources that can increase learning motivation, such as learning materials and support from family.  The findings are expected to provide a perspective for universities to design programs that have a positive impact on students' learning motivation, especially for those who come from economically disadvantaged backgrounds.